Effect of arginine on proliferation of porcine ovarian granulosa cells and steroid hormone synthesis - Zhang, Tianrui; Lu, Xintan; Wang, Xinyi; Liu, Zebei; Shao, Xuwen; Han, Rui; Che, Dongsheng (Frontiers in Veterinary Science, 2026)
Granulosa cells of the ovary (GOC) served as a core component of the follicular microenvironment, playing a crucial role in regulating steroid hormone synthesis and maintaining pregnancy initiation during key reproductive processes. Arginine (Arg) was a key amino acid in follicular fluid that played a potential role in regulating animal reproduction. However, the mechanism by which it controlled the secretion of steroid hormones by ovarian granulosa cells during the initiation of pregnancy remained unclear. In this study, primary porcine ovarian granulosa cells were used to investigate the effects of arginine on cell proliferation, steroid hormone synthesis, and the underlying molecular mechanisms related to pregnancy maintenance. Results showed that the average arginine concentration in follicles measuring 3–8 mm in diameter was 2.7 mM. Based on these measurements, five arginine supplementation groups were established. Findings indicated that the 4.2 mM arginine group exhibited the highest granulosa cell proliferation efficiency, significantly higher than the control group (p < 0.01). The 4.2 mM arginine group significantly upregulated the expression of genes related to cell proliferation, cell cycle, and apoptosis. Concurrently, the 4.2 mM arginine group upregulated the expression of steroid hormone synthesis-related genes CYP11A1 (p < 0.01) and STAR (p < 0.01), thereby promoting estradiol synthesis. Transcriptome sequencing revealed the molecular mechanism by which arginine promoted proliferation and hormone secretion in porcine ovarian granulosa cells. The study found that arginine significantly upregulated the expression of STARD3 and STARD6, key genes in the cholesterol metabolism pathway. This study underscored the pivotal function of arginine in the regulation of reproduction, elucidating its influence on cellular cholesterol metabolism, the promotion of porcine ovarian granulosa cell proliferation, the inhibition of apoptosis, the enhancement of cellular activity, and the facilitation of steroid hormone synthesis through the mediation of STARD3 and STARD6.